2013
DOI: 10.1161/circgenetics.111.962613
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Partial and Complete Loss-of-Function Mutations in Endothelial Lipase on High-Density Lipoprotein Levels and Functionality in Humans

Abstract: Background— Endothelial lipase is a phospholipase with activity against high-density lipoprotein. Although a small number of mutations in LIPG have been described, the role of LIPG in protection against atherosclerosis is unclear. Methods and Results— We identified 8 loss-of-function (LOF) mutations in LIPG in individuals with h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
42
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 44 publications
4
42
1
1
Order By: Relevance
“…HDL (n=95), non-HDL (n=100), genome-wide association studies (GWAS; n=97), and non-GWAS (n=98) lipid genes are defined in Table I in the online-only Data Supplement. Size and the number of rare variants identified in each subset of the lipid geneset are presented in Table VIII in the online-only Data Supplement. by guest on May 11, 2018 http://atvb.ahajournals.org/ Downloaded from the established HDL genes are casually related to the extreme HDL-C phenotypes in our patient cohort and that, consistent with previous studies, 9,11,29 most of the affected individuals did not have a rare variant in a well-established HDL gene.…”
Section: Rare Variants In Established Hdl Genes Are Casually Related supporting
confidence: 91%
See 1 more Smart Citation
“…HDL (n=95), non-HDL (n=100), genome-wide association studies (GWAS; n=97), and non-GWAS (n=98) lipid genes are defined in Table I in the online-only Data Supplement. Size and the number of rare variants identified in each subset of the lipid geneset are presented in Table VIII in the online-only Data Supplement. by guest on May 11, 2018 http://atvb.ahajournals.org/ Downloaded from the established HDL genes are casually related to the extreme HDL-C phenotypes in our patient cohort and that, consistent with previous studies, 9,11,29 most of the affected individuals did not have a rare variant in a well-established HDL gene.…”
Section: Rare Variants In Established Hdl Genes Are Casually Related supporting
confidence: 91%
“…by guest on May 11, 2018 http://atvb.ahajournals.org/ Downloaded from readily clarified. For example, 2 splice-site variants in APOC3 most probably gave rise to increased HDL-C in these patients as a direct consequence of enhanced lipoprotein lipase-mediated plasma triglyceride hydrolysis.…”
Section: Rare Variants In Genes Not Directly Associated With Hdl Metamentioning
confidence: 99%
“…80 Like HL, EL has also been shown to be capable of bridging HDL and other lipoproteins with cell surface proteoglycans. 202 An association between LIPG variation and HDL-C levels has been confirmed through GWAS, 77,203 and several studies suggest that mechanisms underlying the associations between the LIPG SNPs and HDL metabolism may involve loss of function 204 as well as impaired secretion of EL, both resulting in elevated levels of HDL-C. 205 Singaraja et al 206 identified and functionally characterized several partial and complete lossof-function LIPG mutations. Their impact on HDL-C is directly related to their effect on loss of EL function, supporting the hypothesis that antagonism of EL function would provide cardioprotection.…”
Section: Endothelial Lipasementioning
confidence: 94%
“…The heterogeneity of the vascular effects of HDL may be attributed to changes in the HDL-associated proteome and lipids, i.e., posttranslational protein modifi cations and changes in the amount and type of proteins and lipids bound to the HDL particle. In particular, HDL is susceptible to oxidation/ modifi cation in vitro by a variety of oxidants, such as metal with a reduced risk of coronary disease or myocardial infarction, although this does not apply for all associations [e.g., cholesteryl ester transfer protein (CETP )], and for some genes remains inconclusive ( 20,21 ).…”
mentioning
confidence: 99%